Supervivencia y crecimiento larval de Arbacia punctulata (Echinodermata: Echinoidea) alimentada con cinco microalgas a dos salinidades - García, Mariana (2005)
Larval survival and growth of Arbacia punctulata (Echinodermata: Echinoidea) fed with five micro-algae at two salinities. Fertilized eggs from an spontaneously spawn of thirty sexually mature sea urchins (Arbacia punctulata) were incubated to complete embryonic development. The echinopluteus larvae (3 ind/ml) were distributed into 50 plastic containers (25 containers at 30 psu and 25 containers at 40 psu) and fed on Tetraselmis chuii, Nannochloropsis oculata, Isochrysis galbana, Chaetoceros gracilis and C. calcitrans under a natural photoperiod. The water of the containers was partially renewed (75%) everyday. Larval anatomic development aspects, daily survival and growth were determined. The growth was determined through postoral arms and body length measurement, and body diameter of twelve larvae during metamorphosis. During the planktonic larval phase, only the I. galbana diet produced similar results for both salinities. The relative growth of larvae was isometric (I) for larvae fed on I. galbana at two salinities and positive allometric for those fed on C. gracilis and C. calcitrans at both salinities. In this study A. punctulata started metamorphosis at day 14 and was completed 30 days after fecundation. Significant differences were detected in post-settlement body growth between the two salinities (F=23.58, p<0.05): growth was better for larvae at 30 psu (final body diameter was 3.14 ± 0.44 mm). The final rate of planktonic larvae was highest with I. galbana (58.33%). For juveniles the rate was 6.48% for those fed on C. gracilis (40 psu in both larvae and juveniles). We recommend the use of this diet and 40 psu for survival or 30 psu for growth. Rev. Biol. Trop. 53(Suppl. 3): 329-336. Epub 2006 Jan 30.